Flexible 3D Plasmonic Web Enables Remote Surface Enhanced Raman Spectroscopy - Erika Rodríguez‐Sevilla; Jonathan Ulises Álvarez‐Martínez; Rigoberto Castro‐Beltrán; Eden Morales‐Narváez (Advanced Science, 2024)
Abstract Nanoplasmonic materials concentrate light in specific regions of dramatic electromagnetic enhancement: hot spots. Such regions can be employed to perform single molecule detection via surface‐enhanced Raman spectroscopy. However, this phenomenon is challenging since hot spots are expected to be highly intense/abundant and positioning of molecules within such hot spots is crucial to manage with ultrasensitive SERS. Herein, it is discovered that a 3D plasmonic web embedded within a biohybrid (3D‐POWER) exhibits plasmonic transmission, spontaneously absorbs the analyte, and meets these so much needed criteria in ultrasensitive SERS. 3D‐POWER is built with nanopaper and self‐assembled layers of graphene oxide and gold nanorods. According to in silico experiments, 3D‐POWER captures light in a small region and performs plasmonic field transmission in a surrounding volume, thereby activating a plasmonic web throughout the simulated volume. The study also provides experimental evidence supporting the plasmonic field transport ability of 3D power, which operates as a SERS signal carrier (even beyond the apparatus field of view), and the ultrasensitive behavior of this ecofriendly and flexible material facilitating yoctomolar limit of detection. Besides, 3D‐POWER is proven useful in food and biofluids analysis. It is foreseen that 3D‐POWER can be employed as a valuable platform in (bio)analytical applications.